STUDENTS’ ATTITUDES TOWARD ENGLISH AND THEIR ACHIEVEMENT IN SENIOR HIGH SCHOOL - A CORRELATION STUDY - Nurohmat Nurohmat; Rewindinar; Dian (LPPM Universitas PGRI Jombang, 2026)
This study aims to analyze the relationship between students' attitudes toward English learning and their English achievement at the senior high school level. A quantitative correlational approach was employed, with a sample of 86 high school students in Jakarta selected via simple random sampling. Data were collected using a validated 20-item Likert-scale attitude questionnaire, measuring affective, cognitive, and conative components, and documentation of academic scores from semester report cards. Pearson correlation analysis revealed a significant positive relationship (r = 0.724, p = 0.001) between students' attitudes and their academic achievement. The findings suggest that positive attitudes, encompassing interest, motivation, and self-confidence, play a crucial role in enhancing English learning outcomes by potentially lowering the affective filter and increasing engagement. This study provides practical implications for pedagogical strategies, curriculum design, and school policy, emphasizing the need to foster positive affective domains in English language teaching to enhance learning quality in the Indonesian senior high school context.